Implementasi JST Pada Keamanan Data Smartphone menggunakan metode metode Bidirectional associative memory BAM - Yendrizal, Yendrizal (LPPM UNIKA Santo Thomas Medan, 2023)
The development of smartphone technology is currently increasing from year to year, this can be seen from the many outputs of smartphone technology circulating in the market. Smartphones are now a primary need for carrying out daily life. Smartphones are used not only for communication but also for data storage. The research problem often occurs when data is stolen from smartphones from criminal acts. The purpose of this study is pattern recognition on smartphones according to the user's secret key to avoid data theft and other criminal acts. Pattern recognition uses the BAM Continuous Associative Memory Bidirectional method using Activation and sigmoid functions. The Smartphone recognition pattern consists of 5 patterns namely Z pattern, O pattern, M pattern, O pattern and W pattern. The pattern results obtained from Z=[7,7] pattern, O=[11,15] pattern, M=[ pattern 13,7], pattern X=[7,9], pattern O=[11,15]. Based on the final results after searching for 5 patterns, only pattern Z=[7.7] and pattern X=[7.9] are the same as the expected targets in pattern recognition that were entered.